Comparing straw checkerboards paving methods in deserts of China with sustainability indicators. (October 2019) - Sui, T T; Liu, J H; Huang, T; Huang, Q Q; Wang, D; Ma, K
Abstract: The straw checkerboard sand barrier (SCSB) is widely used to fix sand and prevent desertification n China. In this paper, two methods of straw checkerboard (SC) paving are compared using sustainability indicators: the traditional method employing workers using straw and shovel, and the mechanized method using straw and a sand fixing vehicle. The paper describes the processes of the two different paving methods. Data regarding these two different methods of SC0020 paving were obtained from prior research experiments conducted by a sand-fixing vehicle prototype. The paper proceeds to use three sustainability indicators representing the three aspects of sustainable development. Using these indicators, data were compared to assess these two methods. The results show that the operational efficiency of the mechanized method is nearly 200 times higher than the traditional method, and that the total cost in the operational process can be reduced by about 7, 200 Yuan (about 1, 145 USD) per hectare. The completion cycle of the break-even point (164 hectares) is 52.5 days in mechanized method, which is about one tenth of the traditional method. This not only indicates a clear advantage of performance and cost-effectiveness for the mechanized process over the traditional method, but also shows that this mechanized process can contribute to sustainable development for the region greatly because the preliminary work on degraded land and soil restoration can be completed in a significantly shorter period and the health conditions of a large number of manual workers can be improved.